Efficient Electrolytes for Lithium–Sulfur Batteries - Angulakshmi, Natarajan; Stephan, Arul Manuel (Frontiers in Energy Research, 2015)
This review article mainly encompasses on the state-of-the-art electrolytes for lithium–sulfur batteries. Different strategies have been employed to address the issues of lithium-sulfur batteries across the world. One among them is identification of electrolytes and optimization of their properties for the applications in lithium-sulfur batteries. The electrolytes for lithium-sulfur batteries are broadly classified as (i) non-aqueous liquid electrolytes, (ii) ionic liquids, (iii) solid polymer and (iv) glass-ceramic electrolytes. This article presents the properties, advantages and limitations of each type of electrolytes. Also the importance of electrolyte additives on the electrochemical performance of Li-S cells is discussed.